Association of thyroid disease with risks of dementia and cognitive impairment: A meta-analysis and systematic review - Ma, Li-Yun; Zhao, Bing; Ou, Ya-Nan; Zhang, Dan-Dan; Li, Qiong-Yao; Tan, Lan (Frontiers in Aging Neuroscience, 2023)
Introduction It is still uncertain whether the risk of dementia and cognitive impairment is related to thyroid disease. we carried out a meta-analysis and systematic review (PROSPERO: CRD42021290105) on the associations between thyroid disease and the risks of dementia and cognitive impairment. Methods We searched PubMed, Embase, and Cochrane Library for studies published up to August 2022. The overall relative risk (RRs) and its 95% confidence interval (CIs) were calculated in the random-effects models. Subgroup analyses and meta-regression were conducted to explore the potential source of heterogeneity among studies. We tested and corrected for publication bias by funnel plot-based methods. The Newcastle-Ottawa Scale (NOS) or Agency for Healthcare Research and Quality (AHRQ) scale were used to evaluate the study quality of longitudinal studies and cross-sectional studies, respectively. Results A total of 15 studies were included in our meta-analysis. Our meta-analysis showed that hyperthyroidism (RR = 1.14, 95% CI = 1.09–1.19) and subclinical hyperthyroidism (RR = 1.56, 95% CI = 1.26–1.93) might be associated with an elevated risk for dementia, while hypothyroidism (RR = 0.93, 95% CI = 0.80–1.08) and subclinical hypothyroidism (RR = 0.84, 95% CI = 0.70–1.01) did not affect the risk. Discussion Hyperthyroidism and subclinical hyperthyroidism are predictors of dementia. Systematic review registration PROSPERO, Identifier: CRD42021290105.